2010
DOI: 10.1086/650749
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Course Raltegravir Intensification Does Not Reduce Persistent Low‐Level Viremia in Patients with HIV‐1 Suppression during Receipt of Combination Antiretroviral Therapy

Abstract: Background Combination antiretroviral therapy suppresses but does not eradicate human immunodeficiency virus type 1 (HIV-1) in infected persons, and low-level viremia can be detected despite years of suppressive antiretroviral therapy. Short (28d) course antiretroviral intensification of standard combination therapy is a useful approach to determine whether complete rounds of HIV-1 replication in rapidly cycling cells contribute to persistent viremia. We investigated whether intensification with the integrase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
127
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(142 citation statements)
references
References 42 publications
15
127
0
Order By: Relevance
“…This residual viremia was not reduced by treatment intensification (10,11,18). However, these results are under debate (8), as it has been suggested that residual viremia does not arise from ongoing cycles of HIV-1 replication and infection of new cells.…”
Section: Discussionmentioning
confidence: 99%
“…This residual viremia was not reduced by treatment intensification (10,11,18). However, these results are under debate (8), as it has been suggested that residual viremia does not arise from ongoing cycles of HIV-1 replication and infection of new cells.…”
Section: Discussionmentioning
confidence: 99%
“…Through in-depth phylogenetic analyses, we determined that the HIV-1 reservoir in these cells from eight patients is kept stable during long-term cART and, with little evidence of viral replication, this population could be maintained by homeostatic cell proliferation or other processes. (30,31), suggesting that cART is effective in preventing viral replication in these anatomical sites. In contrast, increased numbers of 2-long terminal repeat circles in peripheral blood mononuclear cells and decreased amounts of unspliced HIV-1 RNA in CD4 + T cells isolated from the terminal ileum have been reported during raltegravir intensification, supporting the concept that some viral replication can occur despite suppressive cART (32,33).…”
Section: Significancementioning
confidence: 99%
“…The level of viremia is not affected by the inclusion of another drug. Several studies have been performed in which a suppressive three-drug regimen was intensified by the addition of a fourth inhibitor of a class previously unseen by the patient (Dinoso et al 2009;Gandhi et al 2010;McMahon et al 2010). Despite some differences in design and inhibitors used, all studies gave the same result: There was no difference in the amount of virus during and after the intensification period as compared with before.…”
Section: Persistence Of Hiv-1 Infection On Therapymentioning
confidence: 99%